الاختلاف في تفسير المصطلحات الأصولية وأثره في اختلاف النقل عن أئمة المذاهب الأربعة في الأصول الإجماع السكوتي نموذجا (Revue El-Wahat pour les Recherches et les Etudes, 2020)
The Controversial Reports From The Four Ousoul School Scholars Has Many Causes Which Shouldn’t Be Ignored By The Charia Student , As The The Difference In Explaining Some Ousoul Terminologies Is The Main Cause Which Led To The Controversy Among The Four School Scholars In The Ousoul Of Filh ( Bases Of Filh).                                                      This Current Study Aims To Determine To What Extent Does The Controversy Of Explaining The Ousoul Terminologies Effect On The Reporting From The Four School Scholars About Ousoulfihl Issues           .Indeed, I Have Exposed The Term : The Non Said Consensus As A Detailed Example To Show The Impact Of Ousoul Scholars Controversy To Explain Its Meaning In Particular Their Controversy In Explaning The Opinion Of Imam El Chafiiabout Its Authenticity And Weather It Is A Real Consensus Or Not . Key Words - Controversy , Ousoul Terminology , The Four Scholars , The Non Said Consensus